The Effect of Applying PQ4R Strategy with a Scientific Approach on Mathematical Problem Solving Ability - Emy Artuti (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: This study aims to determine the effect of applying the PQ4R strategy with a scientific approach to the ability to solve mathematical problems in social arithmetic material. Methodology: This research method is quantitative. The research that will be used is true experimental research. In this study, there were 2 sample class groups, namely the experimental and control classes. The author will provide learning treatment using the PQ4R learning strategy with a scientific approach to the experimental class, while the control class, it remains with the usual expository strategy. Main Findings: Based on the results of student activity research, it was obtained that 80% of students were active from the total number of students. Then the assessment results of student activity observation sheets are included in the "Very Good" category. The results mentioned above have achieved the criteria for success in a lesson so that the use of the PQ4R learning strategy (Preview, Question, Read, Reflect, Recite, Review) affects the learning process of student activities. Novelty/Originality of this study: The novelty of this research is the use of PQ4R learning strategies in fostering students' problem-solving abilities in mathematics.